Adsorption of acetic acid and hydrogen sulfide using NaOH impregnated activated carbon for indoor air purification. Issue 1 (14th January 2020) - Wang, Shuang; Nam, Hoseok; Gebreegziabher, Tesfay Berhe; Nam, Hyungseok
Abstract : Excessive exposure to hydrogen sulfide (H2 S) and acetic acid (CH3 COOH) gases is extremely dangerous in a confined space. An effective indoor air pollutant removal porous carbon filter was developed using NaOH impregnated on activated carbon (NaOH/AC) for the adsorption of H2 S and CH3 COOH. Activated carbon (NaOH/AC) filter was characterized using various methods, indicating good physical and chemical properties (especially ‐OH functional groups) for the adsorption of air pollutants. The prepared NaOH/AC filter was cured at different curing temperatures and residence times to understand the effect of the curing conditions on the adsorption performance. The best results were obtained with NaOH/AC filter cured at 100°C for 20 minutes as it eliminated the initial concentration of 400 ppm of CH3 COOH in 15 minutes and H2 S in 30 minutes at 20°C and 60% relative humidity. Isotherm and kinetic models were used to analyze the adsorption process. Langmuir isotherm and pseudo‐second order kinetic models provided the best fit to the adsorption of CH3 COOH and H2 S on NaOH/AC filter. The adsorption mechanism was controlled by the intraparticle diffusion combined with film diffusion. The maximum adsorption capacity of NaOH/AC filter was 473 mg/g for H2 S adsorption, and 550 mg/g for CH3 COOH adsorption. In addition, the spent NaOH/AC filter was regenerated for reuse. This study is expected to develop low‐cost and effective porous carbon filter using NaOH‐modified activated carbon for indoor air purification. Abstract : A low‐cost and effective indoor air pollutant adsorption technology was fabricated by impregnating NaOH on activated carbon for the removal of CH3COOH and H2S. The surface of the NaOH‐impregnated activated carbon filter revealed many adsorption active sites and functional groups (–OH). The maximum adsorption capacities achieved for H2S and CH3COOH were 473.33 mg/g and 550.48 mg/g, respectively.